THE PRACTICE OF FAIR TRANSACTION ON PROPERTY BUSINESS: A CASE ON ISLAMIC PROPERTY COMPANY - Aziz, Abd (universitas Islam Zainul Hasan Genggong, 2023)
Pasuruan, known for its industrial area (PIER), has attracted many investors to inject capital into various sectors. This situation has brought positive impacts, such as increased employment opportunities for both local residents and migrants who have settled in Pasuruan. However, it has also created challenges, particularly regarding the growing demand for housing. Sharia property businesses offer a promising solution by engaging in the buying and selling of land plots and houses, based on financing concepts that avoid exploitation and aim to make it easier for consumers to invest for both business and residential purposes. This research employs a qualitative method with a case study approach, aiming to present the condition of the property business and comprehensively analyze it based on Islamic financing principles. From the initial data analysis, it was found that the land plot sales of Aflaha Property Syariah face threats from emerging competitors in both conventional and sharia financing businesses. To address this, it is necessary to further enhance customer satisfaction through various sharia contracts such as murabahah, ijarah muntahiya bit-tamlik, and musyarakah mutanaqisah, while also accelerating the issuance of land and shop ownership certificates. Importantly, these strategies should still uphold the principle of ta'awun (mutual cooperation) in every transaction. This research provides an empirical study of fair transactions in the property business, which can serve as a valuable input for future related research and offer recommendations to relevant stakeholders. Property Company